Influence of managerial ethical values on perceived earnings quality: evidence from Japan / Masumi Nakashima - Nakashima, Masumi (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2023)
This paper explores whether managerial ethical values and incentives/ pressures affect perceived earnings quality through structural equation modeling based on responses provided by chief financial officers (CFOs) of public firms in Japan. This study develops the research framework by applying the Theory of Planned Behavior, the Upper Echelon Theory, and the Fraud Triangle Theory. In this model, managerial decisions are viewed as intentions and earnings quality as behavior or the outcome of intentions. In this study, managerial ethical values are quantified as the tone at the top (TATT), and the simultaneous analysis results support my theoretical model and show that subjective norms and behavioral beliefs influence earnings management intentions. It was found that perceived TATT has a significant and positive effect on perceived earnings quality, and perceived incentives/pressures have a significant negative influence on perceived earnings quality. Overall, my model implies that since incentives/pressures induce management to improve earnings quality, individuals with stronger ethical values should be appointed as managers; moreover, an ethical environment can be fostered by strengthening accounting standards.